Optimising Fungal Spore Cultivation and Inoculation Methods for Enhanced Antifungal Performance Testing of Textiles - Hongying Deng; Chen Yang; Zhenzhu Zhang; Xiaoling Xu; Qixuan Chen; Yanan Zhang; Xuefen He (Textile & Leather Review)
To improve the precision and operability of antifungal performance testing, this study systematically examines the cultivation time, spore suspension preparation, and inoculation protocols for fungal spores commonly used in mildew and rot resistance testing. Key optimisations were achieved in inoculum time, centrifugation conditions, and spray inoculation methods, enhancing experimental reliability. The findings indicate that Aspergillus brasiliensis and Trichoderma lignorum spores form abundantly within 5–7 days, while Chaetomium globosum requires 17–20 days. Penicillium funiculosum, Aureobasidium pullulans, Paecilomyces variotii, and Trichoderma virens reach sufficient spore production in 13–15 days. Effective spore separation was achieved via centrifugation at 6000 r/min for 10 minutes. Uniform and quantitative spore inoculation was ensured using 20–50 μm spray nozzles. Quantitative methods, including specific turbidity, hemocytometer counting, and the plate count method, were evaluated, with turbidity and hemocytometer methods offering efficiency and simplicity, while plate counts provided verification. These findings contribute to establishing standardised and reproducible antifungal testing procedures, addressing operational guidelines gaps and supporting the development of antifungal technologies.